Pengawasan Lembaga Ombudsman DIY terhadap Sektor Pendidikan Tahun 2023-2024 - Sawa Assabila; Nurmalita Ayuningtyas Harahap (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This research study discusses the role, obstacles, and solutions of Lembaga Ombudsman DIY (LO DIY) in overseeing the education sector in 2023-2024. The research typology used is normative-empirical legal typology. The data analysis used is qualitative data analysis. The results of the study are first, LO DIY followed up on reports of alleged maladministration in sector education and exercises authority on its own initiative, in 2023-2024 several forms of maladministration in the education sector were found. However, there is a downward trend due to constant warnings by LO DIY itself and cooperation with Dinas Pendidikan Pemuda dan Olahraga DIY in PPDB policy and supervision. Second, the obstacles faced by LO DIY include preference for direct complaints, budget limitations due to refocusing, lack of understanding of the applicable legal regulations, and recommendations that are less legally binding.